Knowledge and attitudes of patients towards selfmedication with macrolide antibiotics (Journal of Pharmaceutical Negative Results, 2022)
The research aimed to: Establish a connection between the level of knowledge and behavior against self-medication with macrolide-type antibiotics in patients. A non-experimental, cross-sectional, descriptive and correlative study was carried out with a basic deductive research design of 600 participants, an observational model and a population that differs from the sample. The survey technique was used to collect data on the level of knowledge and attitude towards self-medication, applying the Likert and Dichotomous scale. A statistical procedure was used, creation of contingency tables, bar graphs, analysis and interpretation. Applying Spearman's correlation coefficient whose value for validation, rs = 0.504, shows a high positive correlation. Determining p value = 0